EFFECT OF TEMPERATURE, PH ON TOTAL CONCENTRATION AND COLOR STABILITY OF ANTHOCYANINS COMPOUND EXTRACT ROSELLE CALYX (HIBISCUS SABDARIFFA L.) - R, Hermawan (Jurusan Kimia, Fakultas Sains dan Teknologi UIN Maulana Malik Ibrahim Malang, 2012)
Recently, Roselle (Hibiscus sabdariffa L.) has been known as communities used for tea, rather than based on this background, research was conducted with the aim: (1) To determine the rate of anthocyanin degradation due to the influence of heating and color stability extract roselle calyx (Hibiscus sabdariffa L.), (2) To determine the stability of anthocyanin due to the influence of pH on total anthocyanin extract compounds and color roselle calyx (Hibiscus sabdariffa L.) during the storage process. This research was conducted by extracting the sample with citric acid 2% solvent. Concentrated extract was used to test the stability of the heating temperature, test the stability of pH during the storage process for ± 30 days and color change. The results of this study indicate that extracts of roselle calyx (Hibiscus sabdariffa L.) experienced a decrease in concentration at 80 °C. Concentration of anthocyanin degradation rate followed the equation r = 0.014T – 1.169 with the lowest concentration value of 32.916 mg / L. The intensity of color produced due to the influence of heating at 80 °C with varying time is 29.6 to 30.7 for the parameters of brightness (L *), 23.9 to 20.7 redness (a *), and 13.5 - parameter 15 for yellow (b *) increased. The intensity of color produced due to the influence of pH variation during the storage process is 27.5 to 26.2 for L * values decreased on average instead of L * at different pH average value increased from 27.5 to 39.7 . The result of reading the value of a * decreased with increasing storage time and reduced levels of acidity, namely from 22.7 to 18.3 and from 22.7 to 9.7. While reading the value of b * along with increasing storage duration has decreased and has decreased with the reduction in the level of acidity, namely from 11.8 to 10.9 and from 11.8 to 13.8. Keywords: Roselle (Hibiscus sabdariffa L.), anthocyanins, degradation, temperature, pH, color